PHP and MySQL Web Development : a beginner's guide - Matthews, Marty (New York : McGraw-Hill Education, 2015)
"This step-by-step tutorial shows you how to use PHP and MySQL to power websites with dynamic content. PHP and MySQL Web Development: A Beginner's Guide takes you from building static pages to ones with PHP and MySQL dynamic elements. Hands-on projects get you started using new skills right away!This solutions-oriented book is organized around real-world web scenarios that demonstrate the use of PHP and MySQL. These scenarios can be directly used to build web pages with dynamic content. Security topics such as validation, authentication, and encryption are addressed throughout. Each chapter teaches practical techniques that can be immediately applied Covers the basics of what drives many of today's most popular sites Ready-to-use code examples from the book available for download "--
Machine generated contents note: Part I: Getting Ready -- Ch 1: Setting Up Your Programming Workstation -- Ch 2: Building Web Pages with HTML -- Ch 3: Using CSS and Templates -- Ch 4: Adding Dynamic Elements with JavaScript -- Part II: Exercising the Server with PHP -- Ch 5: Introduction to PHP -- Ch 6: Fundamentals of PHP -- Ch 7: Reading and Writing Files -- Ch 8: User Authentication and Error Handling -- Part III: Creating and Using a Relational Database with MySQL -- Ch 9: Introduction to Databases, SQL, and MySQL -- Ch 10: Fundamentals of MySQL -- Ch 11: Adding, Modifying, and Deleting Tables and Records -- Part IV: Powering Databases with PHP and MySQL -- Ch 12: Connecting to and Accessing a MySQL Database with PHP -- Ch 13: Registering Users and Responding to Their Needs -- Ch 14: Providing For and Handling Online Purchases.
Includes index.
Keywords: PHP (Computer program language); MySQL (Electronic resource); Web site development; COMPUTERS / Programming / General